Halogen-free transparent thermoplastic elastomer material as well as preparation method and application thereof
By adding specific components to the thermoplastic elastomer material, the problems of low environmental protection and high thermal welding temperature of traditional PVC catheters are solved, and the high mechanical strength and low-temperature thermal welding performance of halogen-free transparent thermoplastic elastomer materials are achieved. Application of in vitro catheters.
Patent Information
- Application Number
- CN202411531625.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Traditional PVC catheters have problems such as low environmental protection, high thermal welding temperature and low mechanical strength, and it is difficult to replace the application of thermoplastic elastomers in medical devices.
By adding styrene block copolymer, linear low-density polyethylene and olefin copolymer to the thermoplastic elastomer material, and optimizing the component ratio, halogen-free with high mechanical strength and dimensional stability is obtained. Transparent thermoplastic elastomer material can be thermally welded with PVC materials at lower temperatures.
The high mechanical strength, dimensional stability and low-temperature thermal welding performance of halogen-free transparent thermoplastic elastomer materials are achieved, avoiding the risk of high-temperature deformation, and improving the connection stability and safety of the catheter.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and more specifically to a halogen-free transparent thermoplastic elastomer material and a preparation method and application thereof. Background Art
[0002] With the improvement of medical level, the requirements for medical equipment, instruments and consumables are getting higher and higher. Some patients who are unable to defecate on their own after surgery need to use a catheter bag to store urine and then discharge urine through a catheter. Traditional catheters are made of PVC material and have good flexibility, but PVC catheters contain chlorine (Cl) elements, which are not environmentally friendly. They will release toxic halide gas under heating conditions, which is harmful to human health.
[0003] Thermoplastic elastomers have good thermal stability, soft touch, low odor and emission, safety and non-toxicity, and are ideal substitutes for PVC urinary catheters. However, thermoplastic elastomers have low mechanical strength and low dimensional stability, which affects the connection stability between medical tubes. In addition, the melting point of thermoplastic elastomers is high, so the temperature required for thermal welding of thermoplastic elastomer urinary catheters and PVC urinary catheter bags is too high, resulting in the risk of PVC urinary bags being deformed by high temperature in actual applications, affecting the safety of use.
[0004] Patent CN115926282A discloses a polyolefin composite material and its preparation method, a heat shrinkable tube and a medical device. The raw materials for preparing the polyolefin composite material include polyolefin, ethylene-vinyl acetate copolymer and an anti-burning agent, and a polyolefin composite material with high impact strength and good elasticity is prepared. The heat shrinkable tube prepared by the polyolefin composite material is arranged on a medical catheter, which can improve stability and service life, thereby improving the safety of use when applied to medical devices. However, the main raw material component of the polyolefin composite material is a polyolefin with a relatively high melting point, which is not easy to be thermally welded with a PVC material and is not suitable for use in a urinary catheter material. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects and shortcomings of existing transparent thermoplastic elastomers and provide a halogen-free transparent thermoplastic elastomer material which is halogen-free and environmentally friendly, has high mechanical strength and dimensional stability, and can be thermally welded with PVC materials at a relatively low temperature.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned thermoplastic elastomer material.
[0007] Another object of the present invention is to provide a use of the above-mentioned thermoplastic elastomer material in the preparation of an extracorporeal urinary catheter.
[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0009] The present invention protects a thermoplastic elastomer material, comprising the following components in parts by weight:
[0010]
[0011] The olefin copolymer elastomer is ethylene-vinyl acetate copolymer (EVA), and the VA content is ≥25wt%.
[0012] The present invention obtains a halogen-free transparent thermoplastic elastomer material with suitable Shore hardness, high tensile strength and dimensional stability by compounding a styrene block copolymer, a linear low-density polyethylene (LLDPE) and an olefin copolymer elastomer and optimizing the component ratio; the thermoplastic elastomer material can be thermally welded with a PVC material at ≤100°C and has high bonding strength.
[0013] Among them, the use of styrene block copolymers and EVA compounding can have good compatibility with PVC materials. At the same time, adding a specific amount of LLDPE can effectively improve the tensile strength of the material, making it less likely to leak when using a catheter, enhancing dimensional stability, and having little effect on the low-temperature thermal welding performance of the material and PVC. More importantly, by controlling the VA content in EVA, the entire component system can achieve thermal welding performance with PVC materials at a lower temperature (≤100°C) and has higher adhesion. In addition, rubber plasticizers and lubricants effectively improve the plasticization and processing properties of the material, improve dimensional stability, and reduce the inner and outer diameter tolerances of the extruded pipe.
[0014] In some embodiments, the thermoplastic elastomer material has a Shore hardness of 60-85A, preferably 68-80A, a tensile strength of ≥6.1Mpa, an outer diameter tolerance of ≤0.15mm, an inner diameter tolerance of ≤00.19mm, and a peeling force of hot pressing with PVC at low temperature (100°C) of ≥190N.
[0015] In some embodiments, the melting point of the ethylene-vinyl acetate copolymer is ≤75°C, preferably 65-75°C.
[0016] In some embodiments, the melting point of LLDPE is ≤ 125°C, preferably 118-123°C.
[0017] In some embodiments, the content of the olefin copolymer elastomer that can achieve the purpose of the present invention can be 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, and 40 parts.
[0018] In some embodiments, the VA content of the ethylene-vinyl acetate copolymer is 25-40 wt %.
[0019] In some embodiments, the VA mass percentage content of the ethylene-vinyl acetate copolymer that can achieve the purpose of the present invention can be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, or 40%.
[0020] In some embodiments, the styrene block copolymer is at least one of SBS, SEBS or SEEPS. Preferably, the styrene content in the styrene block copolymer is 25-45 wt.%.
[0021] Preferably, the weight average molecular weight of the styrene block copolymer is ≤120,000; more preferably, the weight average molecular weight is 50,000-120,000.
[0022] Preferably, the melt flow rate of the SEEPS at 230° C. and 2.16 kg is 0.01-0.3 g / 10 min, more preferably 0.02-0.1 g / 10 min. Preferably, the weight average molecular weight is 65,000-85,000, more preferably 72,000-78,000. The degree of hydrogenation of the middle block of the SEEPS is >95%, more preferably, the degree of hydrogenation is >98%. Preferably, the styrene content in the SEEPS is 25-40 wt.%, more preferably 28-32 wt.%. The mass ratio of isoprene to 1,3-butadiene in the SEEPS is (51-59):(41-49), more preferably (54-56):(44-46).
[0023] Preferably, the melt flow rate of the SEBS at 230°C and 5kg is <3g / 10min, more preferably <1g / 10min. Preferably, the weight average molecular weight is 85000-95000, more preferably 87000-92000. The hydrogenation degree of the midblock of the SEBS is >95%, more preferably, the hydrogenation degree is >98%. Preferably, the styrene content in the SEBS is 25-40wt.%, more preferably 28-32wt.%.
[0024] Preferably, the melt flow rate of the SBS at 190° C. and 5 kg is 1-12 g / 10 min, more preferably 4-8 g / 10 min. Preferably, the weight average molecular weight is 60,000-80,000, more preferably 62,000-70,000.
[0025] In some embodiments, the content of the styrene block copolymer that can achieve the purpose of the present invention can be 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, and 37 parts.
[0026] In some embodiments, the content of LLDPE that can achieve the purpose of the present invention can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, and 30 parts.
[0027] In some embodiments, the rubber plasticizer is at least one of silicone oil, paraffin oil, cycloalkane oil or aromatic hydrocarbon oil.
[0028] Preferably, the kinematic viscosity of the rubber plasticizer at 40°C is 45-85 mm 2 / s, testing standard GB / T10247.
[0029] More preferably, the paraffin oil has a kinematic viscosity of 75-85 mm at 40°C. 2 / s.
[0030] More preferably, the naphthenic oil has a kinematic viscosity of 45-55 mm at 40°C. 2 / s.
[0031] In some embodiments, the lubricant is at least one of silicone oil, dimethylsiloxane, vinyl bisstearamide, erucamide, oleamide or polyethylene wax. Preferably, the lubricant is at least one of dimethylsiloxane, erucamide and oleamide.
[0032] In some embodiments, the mass ratio of the LLDPE to the olefin copolymer elastomer is 1:(2.5-4).
[0033] In some embodiments, the following components are included in parts by weight:
[0034]
[0035] In some of the embodiments, the thermoplastic elastomer material may further be added with conventional additives in the art, including but not limited to antioxidants, light stabilizers, nucleating agents or crosslinking agents.
[0036] Preferably, the thermoplastic elastomer material of the present invention further contains 0.1-0.5 parts of an antioxidant.
[0037] More preferably, the antioxidant is at least one of 2,6-di-tert-butyl-4-methylphenol, antioxidant 1010, antioxidant 1076, antioxidant 1790, antioxidant 168 and antioxidant 412S.
[0038] The invention protects a preparation method of a thermoplastic elastomer material, comprising the following steps: uniformly mixing various raw material components in a formula amount, melt-blending and extruding, and the extrusion temperature is 140-260° C. to obtain the halogen-free transparent thermoplastic elastomer material.
[0039] In some embodiments, the preparation method of the thermoplastic elastomer material of the present invention comprises the following steps: uniformly mixing the raw material components of the formula, adding them into a twin-screw extruder with a length-to-diameter ratio of not less than 46:1 through a feeding metering scale, the rotation speed of the twin-screw extruder is 180-450 rpm, the total feed of the metering scale is 80-450 kg / hour, the extruder temperature is set to a range of 140°C-260°C, the material is plasticized by the twin-screw extruder and then enters a cold water tank, and then is pulled into a pelletizer for pelletizing to obtain a finished product.
[0040] The invention protects the use of a thermoplastic elastomer material in the preparation of an extracorporeal urinary catheter. As an extracorporeal urinary catheter, the thermoplastic elastomer material can be welded with a PVC urinary catheter bag at low temperature (≤100°C), effectively avoiding high temperature deformation and having high connection stability.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The present invention provides a halogen-free transparent thermoplastic elastomer material, which adopts the compounding of styrene block copolymer, LLDPE and olefin copolymer elastomer and optimizes the component ratio to obtain a halogen-free transparent thermoplastic elastomer material with suitable Shore hardness, high tensile strength and dimensional stability. Adding a specific amount of LLDPE can effectively improve the tensile strength of the material, and it is not easy to leak when using a catheter, and the dimensional stability is enhanced, and the influence on the low-temperature thermal welding performance of the material and PVC is small. By controlling the VA content in EVA, the entire component system can achieve thermal welding performance with PVC material at a lower temperature (≤100°C) and has a higher bonding force. In addition, rubber plasticizers and lubricants effectively improve the plasticizing performance and processing performance of the material, improve dimensional stability, and reduce the inner and outer diameter tolerances of extruded pipes. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0044] The raw materials used in the following examples and comparative examples are as follows:
[0045] Styrene block copolymer (A):
[0046] A1: styrene-poly(ethylene / ethylene / propylene)-styrene copolymer (SEEPS), Septon 4033, Kuraray Co., Ltd., Japan; melt flow rate at 230°C, 2.16 kg is 0.05 g / 10 min, and the styrene content is 30 wt.%.
[0047] A2: styrene-ethylene-butylene-styrene copolymer (SEBS), Kraton G1650, Kraton Corporation, USA; the melt flow rate at 230°C, 5kg is <1g / 10min, and the styrene content is 30wt.%.
[0048] A3: Styrene-butadiene copolymer (SBS), Globalprene 3546, manufactured by Lee Chang Jung Co.; melt flow rate at 190°C, 5 kg: 6 g / 10 min, styrene content: 40 wt.%.
[0049] B1: Linear low-density polyethylene (LLDPE), DFDA-7042, Guangzhou Petrochemical Company.
[0050] B2: High-density polyethylene (HDPE), JM710, SK Chemicals, South Korea.
[0051] B3: Homopolymer polypropylene, Z30-S, Maoming Petrochemical Company.
[0052] B4: Random copolymer polypropylene, RP 346R, CNOOC Shell Company.
[0053] Olefin copolymer elastomer (C):
[0054] C1: Ethylene-vinyl acetate copolymer (EVA), VA content 18%; ELVAX 460, DuPont Company, USA.
[0055] C2: Ethylene-vinyl acetate copolymer (EVA), VA content 26%; TAISOX 7470M, Taiwan Plastics Corporation.
[0056] C3: Ethylene-vinyl acetate copolymer (EVA), VA content 28%; ELVAX 250, DuPont Company, USA.
[0057] C4: Ethylene-propylene elastomer, VISTAMAXX 3020FL, ExxonMobil Corporation.
[0058] Rubber plasticizer (D):
[0059] D1: paraffin oil, 500N, Formosa Plastics.
[0060] D2: cyclohexane oil, KN4006, Karamay.
[0061] Lubricant (E): Erucic acid amide, ER, Croda, UK.
[0062] Antioxidant (F): Irganox 1010, Irgafos 168, BASF; mixed in a mass ratio of 1:1.
[0063] The preparation method of the halogen-free transparent thermoplastic elastomer material of the following embodiments and comparative examples comprises the following steps: uniformly mixing the raw material components of the formula, adding them into a twin-screw extruder with a length-to-diameter ratio of 46:1 through a feeding metering scale, the speed of the twin-screw extruder is 320 rpm, the total feed of the metering scale is 260 kg / hour, the extruder temperature is set within the range of 140-260°C, the material is plasticized by the twin-screw extruder and then fed into a cold water tank, and then pulled into a pelletizer for pelletizing to obtain a finished product.
[0064] Examples 1 to 9
[0065] This embodiment provides a series of halogen-free transparent thermoplastic elastomer materials, the components of which are shown in Table 1.
[0066] Table 1 Raw material components of Examples 1 to 9 (parts by weight)
[0067]
[0068] Comparative Examples 1 to 8
[0069] This comparative example provides a series of halogen-free transparent thermoplastic elastomer materials, the components of which are shown in Table 2.
[0070] Table 2 Raw material components of comparative examples 1 to 8 (parts by weight)
[0071]
[0072] Performance Testing
[0073] The thermoplastic elastomer material samples of Examples 1-9 and Comparative Examples 1-8 were respectively subjected to the following mechanical property, dimensional stability and PVC adhesive peeling force tests. The test results are shown in Table 3.
[0074] Shore hardness measurement method: add sample particles into the injection molding machine, and injection mold them at 200℃ into a square plate with a length, width and height of 100mm*100mm*2mm respectively. After adjusting at room temperature for 24 hours, stack 3 square plates into a sample with a thickness of 6mm. Use a Shore A hardness tester to measure the hardness of the sample and record it.
[0075] Tensile strength measurement method: According to the test method of standard ISO 37, the prepared sample particles are added to the injection molding machine and processed into a sample plate of 100mm*100mm*2mm size at 200℃. Use a cutter to cut into ISO 37Type 1A size specimens. Use a universal tensile machine to test the specimens prepared in the previous step, and the test conditions are: tensile rate 500mm / min.
[0076] Method for measuring inner and outer diameter tolerance of extruded pipes: Add the prepared sample particles into the extruder, extrude a pipe with an outer diameter of 5.50mm and an inner diameter of 3.50mm at 180°C, take a 10-meter-long pipe, measure its inner and outer diameter dimensions every 1 meter, and record the average dimensional deviation of the outer and inner diameters as the inner and outer diameter tolerance; the unit is mm.
[0077] Test method for adhesion to PVC: Add the prepared sample particles into the injection molding machine, process them into a sample with a size of 100mm*100mm*2mm at 200℃, and prepare the prepared sample. Prepare the PVC sample, and heat press the two samples for 10 seconds at 100℃. After the hot-pressed sample is left to rest for 24 hours, use a universal tensile machine to test the maximum tensile force required for 180° peeling of the elastomer sample and the PVC sample, the unit is Newton (N).
[0078] Table 3
[0079]
[0080] The halogen-free transparent thermoplastic elastomer material of the present invention has a Shore hardness of 68-82A, a tensile strength of more than 6.1 MPa, an outer diameter tolerance within 0.11 mm, an inner diameter tolerance within 0.09 mm, and a peeling force of more than 190 N when hot-pressed with PVC under low-temperature hot welding (100° C.).
[0081] Compared with Example 1, the VA content of ethylene-vinyl acetate copolymer (EVA) in Comparative Example 1 is too low, resulting in a decrease in the peeling force of the material when thermally welded to PVC at 100°C; when the olefin copolymer elastomer in Comparative Example 2 adopts ethylene-propylene elastomer, its peeling force of low-temperature thermal welding (100°C) PVC bonding is significantly reduced.
[0082] Compared with Example 1, when HDPE is used in Comparative Example 3, although the tensile strength can be improved to a certain extent, the peeling force of the low-temperature heat welding (100°C) PVC bonding is greatly reduced. Comparative Examples 4-5 use polypropylene with different structures, and the peeling force of the low-temperature heat welding PVC bonding is reduced. Comparative Example 6 does not contain LLDPE, and its hardness and mechanical properties are significantly reduced.
[0083] Compared with Example 1, when the amount of LLDPE in Comparative Example 7 is excessive, the peeling force of the low-temperature heat welding (100°C) PVC bonding decreases, the dimensional stability deteriorates, and the hardness is too high, which is not easy to bend, and is not conducive to the application in extracorporeal catheters. When the amount of EVA in Comparative Example 8 is excessive, the outer diameter size tolerance and the inner diameter size tolerance become larger, and the dimensional stability deteriorates.
[0084] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A thermoplastic elastomer material, characterized in that: The composition includes the following components in parts by weight: The olefin copolymer elastomer is ethylene-vinyl acetate copolymer, and the VA content is ≥25wt%.
2. The thermoplastic elastomer material according to claim 1, characterized in that: The VA content of the ethylene-vinyl acetate copolymer is 25-40 wt %.
3. The thermoplastic elastomer material according to claim 1, characterized in that: The styrene block copolymer is at least one of SBS, SEBS or SEEPS.
4. The thermoplastic elastomer material according to claim 1, characterized in that: The mass ratio of the LLDPE to the olefin copolymer elastomer is 1:(2.5-4).
5. The thermoplastic elastomer material according to claim 1, characterized in that: The rubber plasticizer is at least one of silicone oil, paraffin oil, cycloalkane oil or aromatic hydrocarbon oil.
6. The thermoplastic elastomer material according to claim 1, characterized in that: The lubricant is at least one of silicone oil, dimethylsiloxane, vinyl bisstearamide, erucamide, oleamide or polyethylene wax.
7. The thermoplastic elastomer material according to claim 1, characterized in that: The composition includes the following components in parts by weight:
8. The thermoplastic elastomer material according to claim 1 or 7, characterized in that: It also includes 0.1 to 0.5 parts of antioxidant.
9. A method for preparing a thermoplastic elastomer material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: uniformly mixing the raw material components in the formula, melting and blending and extruding the components at a temperature of 140-260° C., and obtaining the thermoplastic elastomer material.
10. Use of the thermoplastic elastomer material according to any one of claims 1 to 8 in the preparation of an extracorporeal urinary catheter.
Citation Information
Patent Citations
Light-weight high-elastic EVA composite foamed material and preparation method and application thereof
CN106905599A
Polyolefin elastomer peritoneal dialysis drainage bag cover cap capable of being thermoplastically processed and preparation method of polyolefin elastomer peritoneal dialysis drainage bag cover cap
CN108102201A
High-temperature-resistant and low-temperature-resistant soft sound insulation material and preparation method thereof
CN111925624A
Halogen-free flame-retardant elastomer material, preparation method thereof and optical fiber tail sleeve
CN117247626A
Cited By
Soft thermoplastic elastomer composition and preparation method thereof
CN119798833A